DFT Calculations of Adsorption with Correlations of Atoms on CÃ¢â€šâ€ Ã¢â€šâ‚¬ - Ahmad Zabidi, Noriza; Nazrul Rosli, Ahmad; Abu Kassim, Hasan; Keshav N, Shrivastava; V. Renuka5, Devi (Malaysian Journal of Science, 2008)
Adsorption of all of the atoms from atomic number 1 to 103 is attempted on the center of hexagon of CÃ¢â€šâ€ Ã¢â€šâ‚¬ by using density-functional theory (DFT) in various approximations such as local density approximation (LDA), the generalized gradient approximation with exchange (GGA-X) and the GGA with exchange correlations (GGA-XC). The adsorption energies of 70 different atoms have been calculated successfully. The convergence was not obtained for the 14 rare earths and 11 actinides. Eight different atoms, He, Ne, At, Mn, Fe, Co, Ni and Rn were also not optimized. The Cd and Hg occupied a special place because their adsorption energies were found to be negative, so they do not adsorb in dark but may adsorb when light shines on the system.